Clementi - Devrient, Wilhelm, 1799-after 1866 (engraver):::Creator::::::::::::; Albert, Heinrich (artist):::Contributor:::::::::::: (b. d. Gebr. Schumann; Zwickau; Germany)
Portrait of Muzio Clementi engraved by Wilhelm Devrient based on the drawing by Heinrich(?) Albert.